A spoonful of sugar helps the viruses go down - Francavilla, Ruggiero (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2022)
Studies that attempt to deepen how pathogens try to circumvent the immune system and stimulate understanding of the mechanisms, can boost our knowledge on the process of viral infection, immune response circumvention and disease development. The deepening of this knowledge opens up novel therapeutic and vaccine strategies.